2021
DOI: 10.1128/iai.00738-20
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Cells Provide Mucosal Protection against Gastric Trypanosoma cruzi Infection

Abstract: Trypanosoma cruzi is the intracellular parasite of Chagas disease, a chronic condition characterized by cardiac and gastrointestinal morbidity. Protective immunity requires CD4+ T cells, and Th1 cells and IFN-γ are important players in host defense. More recently, Th17 cells and IL-17 have been shown to exert protective functions in systemic T. cruzi infection. However, it remains unclear whether Th17 cells and IL-17A protect in the mucosa, the initial site of parasite invasion in many human cases. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The macrophages called M1 and M2 looked the same as Th1 and Th2. [37][38][39][40] Such findings suggested that macrophages urging various mouse species had an alternative preference attributable to LPS to produce NO and arginase.…”
Section: Activation and Polarization Of Macrophagesmentioning
confidence: 96%
“…The macrophages called M1 and M2 looked the same as Th1 and Th2. [37][38][39][40] Such findings suggested that macrophages urging various mouse species had an alternative preference attributable to LPS to produce NO and arginase.…”
Section: Activation and Polarization Of Macrophagesmentioning
confidence: 96%
“…Th17 cells, a newly discovered cell type in recent years, play an immunoprotective role against E. granulosus infection by producing inflammatory cytokines (43)(44)(45). IL-17A belongs to one of the most important members of the IL-17 family and is mainly expressed in Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Th17 immune response is important for host defense at the mucosal interface [ 43 ]. In the intestinal mucosa, it has been shown that IL-17A is important for the clearance of bacterial infection [ 44 ]; thus, changes to the local environment due to reduced mucociliary clearance functions in the aged lung may play a role and lead to persistent airway inflammation. These studies implicate neutrophils as a potential contributor to airway inflammation in aging and highlight the relevance of aging rodent models to further interrogate underlying mechanisms.…”
Section: Asthma In the Elderly Pathogenesismentioning
confidence: 99%